KETIADAAN FUNGSI ASAS LEGALITASDALAM HUKUM PIDANA UNTUK MELINDUNGI KEPENTINGAN KORBAN - Deni SB Yuherawan (Arena Hukum, 2013)
Abstract   In practical terms, Principle of Legality perform the function of protection and functionality limitations. The main problems principle of legality is of the absence of protection for victims. The absence of these functions is a logical consequence of the idea of the basic principle of legality in the form of guaranteed protection of the rights of citizens, by limiting the king's power and authority of judges through the instrument of criminal law. Reasons and the main purpose of this idea is to prevent citizens from criminal justice implementation arbitrary. In the life of the law, the legality principle which should give equal protection, was not able to provide protection against the public interest. In ethical life, the legality principle as a principle of law that is supposed to be in the public interest, it turns out more priority to the interests of offenders. Â  Key words:Â  principle of legality, protection function, interests of victims   Abstrak   Secara praktis, Asas Legalitas melakukan fungsi perlindungan dan fungsi pembatasan. Problema utama Asas Legalitas adalah ketiadaan perlindungan terhadap kepentingan korban. Ketiadaan fungsi tersebut merupakan konsekuensi logis dari gagasan dasar  Asas Legalitas berupa  jaminan perlindungan hak-hak warga negara, dengan cara membatasi kekuasaan raja serta kewenangan hakim melalui instrumen undang-undang pidana. Alasan dan tujuan utama gagasan ini untuk menghindarkan warga negara dari pelaksanaan peradilan pidana yang sewenang-wenang. Dalam kehidupan hukum, Asas Legalitas yang seharusnya memberikan perlindungan yang seimbang, ternyata tidak mampu memberikan perlindungan terhadap kepentingan masya rakat. Dalam kehidupan etis, Asas Legalitas sebagai suatu asas hukum yang seharusnya lebih mengutamakan kepentingan masyarakat, ternyata lebih mengutamakan kepentingan pelaku. Kata kunci: Asas Legalitas, fungsi perlindungan, kepentingan korban